PENATAAN KEMBALI KOMPLEKS MUSEUM RADYA PUSTAKA DENGAN PENDEKATAN ARSITEKTUR KONTEKSTUAL DI SURAKARTA - Irma Lovita; Dwi Hedi Heriyanto; Maya Andria Nirawati (Universitas Sebelas Maret Surakarta, 2016)
Radya Pustaka Museum Complex Realignment using Contextual Architecture approach in Surakarta caused by the rapid urban development results in the decrease of the heritage buildings image, especially in Surakarta. Radya Pustaka Museum realignment is an attempt to preserve Radya Pustaka Museum’s existence as one of the oldest museums in Indonesia which preserves Javanese cultural existence proofs in the past. The realignment of the museum complex is conducted by maintaining the shape of Radya Pustaka Museum original building as a conservation effort in which the new object design functions as a new cultural appreciation place done by restoring and developing the function of previous existing activities which were able to accommodate all the museum’s activities and needs. The method used is architecture designing plan method approached by Contextual Architecture. Contextual Architecture is applied as an execution design method with the purpose of creating contextual environment visual harmony between the new building and it previous environment. By using this approach, the form, mass order, and façade elements in the new building are designed by not only aesthetic and contrast appearance, but also contextual to the old one. The realignment is designed in line with Surakarta City Government Planning related to tourism, education, and culture development which are expected to make Radya Pustaka Museum as one of the main representation of the historical aspect of the city and to enact the tourism in the city of Surakarta, as the City of Culture. Also it is expected to improve the quality of life for people both inside and outside the scope of Radya Pustaka Museum complex on an ongoing basis.